Effects of immersion cryotherapy on the performance of Montes Claros volleyball athletes - Santos, Cleidison Costa (2018)
Objective: To investigate and identify the effects of cryotherapy on the performance of Montes Claros volleyball athletes. Method: The census sample consisted of the athletes hired by the team in the 2017/2018 season. The tests were performed in three stages. The first one obtained the values before the training (AT), the second stage obtained the results after the training (DT). In the same one the immersion cryo was carried out and the tests to obtain the acute effects (EA). In the last step, the tests were performed to obtain the chronic effect (EC). Results: When comparing the means between the time of AT and DT, the athletes had a performance reduction with significance of p: 0.024. Between the DT and the EA of the immersion cryo application, the reduction had significance of p: 0.007. After that, the comparison between AT and EC, there was a reduction with significance of p: 0.048. Finally, the comparison between DT and EC was performed, however, it did not present a significant difference. Conclusion: It was concluded that the use of immersion cryotherapy in an acute way is inefficient and counterproductive and there was an improvement in the athlete's performance after the rest weekend and immersion cryo application.